Land inventory of territorial communities as a key element of effective land management - Patiyuk, O.; Fedoruk, A. (Land Management, Cadastre and Land Monitoring, 2021)
The main resource of OTG is land and the most effective management of this resource provides an opportunity to fill the local budget, develop the community, carry out error-free and as clear as possible land management, complying with current legislation while taking into account the interests of the community. It also provides transparency in land management, which increases public confidence in local authorities. If as of today OTG is not provided with complete and up-to-date information on the condition, qualitative and quantitative indicators of community land resources. This does not meet the challenges of today. The lack of an updated cartographic basis and land inventory causes: inability to carry out the process of strategic planning of settlements and communities in general, inability to attract investment, low investment attractiveness of the territory, inability to manage land resources in full, inability to meet the needs of the population. OTG land inventory will allow for a full audit of land resources, and will develop community infrastructure, increase investment attractiveness, will identify all problems that have arisen regarding the management of the community. Key words: united territorial communities, land resources, land inventory, decentralization.